Coal gasification slag enhanced alkali-activated environment-friendly ceramic tile adhesive and preparation method thereof
By adding additives such as modified coal gasification slag powder and plant glue powder to alkali excitation materials, the problems of alkali excitation materials are solved, dry shrinkage cracking and brittleness during the application process, and high early strength and low cost alkali excitation environmentally friendly ceramic tile adhesives are achieved.
Patent Information
- Application Number
- CN202411741029.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-29
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-11-29
AI Technical Summary
Alkaline excitation materials are prone to alkaline, dry shrinkage, cracking and brittleness during application, and commonly used glue powders are prone to failure in alkaline environments, which cannot meet the performance requirements of ceramic tile glue.
The enhanced alkali-excited environmentally friendly ceramic tile adhesive is used to combine alkali-excited materials with modified coal gasification slag powder, plant glue powder and other specific additives to improve the strength and workability of the material and reduce the phenomenon of alkali pancreatic and shrinkage cracking.
It realizes fast coagulation, hardness and high early strength of alkali-activating materials, avoids problems of alkali pancreasing and shrinkage cracking, reduces production costs, and improves bonding strength, and meets the performance requirements of ceramic tile glue.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of building materials, and in particular to a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive and a preparation method thereof. Background Art
[0002] Alkali-activated materials have received extensive attention as a green and environmentally friendly cementitious material, and many new technologies and products related to alkali-activated materials have also emerged. The raw materials for the preparation of alkali-activated materials mainly include industrial solid wastes with potential volcanic ash activity, such as mineral powder and fly ash. When used in combination with alkali activators, cementitious materials with compressive strength equivalent to that of cement, high early strength and better corrosion resistance can be obtained. However, compared with traditional cement, alkali-activated materials, as a new type of material, still need to be verified whether they can meet the requirements in terms of safety and durability if they are to completely replace cement as a structural material. Moreover, alkali-activated materials are often accompanied by problems such as alkali efflorescence, shrinkage cracking and high brittleness during their application, which limits their application.
[0003] As a special mortar, tile adhesive requires a large amount of cement in the preparation process. At the same time, in order to ensure that the mortar has good plasticity and bonding properties, it is necessary to add a variety of organic admixtures that have both water retention and viscosity-increasing effects, resulting in high costs and the early strength of the material needs to be improved. Therefore, people began to study how to use alkali-activated materials to prepare tile adhesives, thereby reducing the amount of cement and material costs.
[0004] However, when using alkali-activated materials to prepare tile adhesives, although organic admixtures can still be added and their water retention and viscosity-increasing effects can be used to improve the problems of alkali-activated materials such as alkali-induced efflux, shrinkage cracking and brittleness, tile adhesives prepared by only replacing cement with alkali-activated materials still have the problems of alkali-induced efflux, shrinkage cracking and brittleness that the alkali-activated materials themselves have; and conventional glue powders are prone to failure in a strong alkaline environment or after being immersed in water and cannot play a role in enhancing the bonding strength, resulting in the adhesive being unable to meet the performance requirements of tile adhesives; in addition, when alkali-activated materials are used instead of cement, in order to ensure the strength of the material, it is often necessary to add a large amount of water glass as an activator to improve the strength of the alkali-activated material, resulting in increased production costs. Summary of the invention
[0005] In view of this, the present invention provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive and a preparation method thereof. The environmentally friendly tile adhesive uses alkali-activated materials instead of cement, and the alkali-activated materials are used in combination with other specific additives, thereby solving the problems of alkali-activated materials being prone to alkali blooming, shrinkage cracking and high brittleness, and the obtained adhesive has the advantages of fast setting and hardening and high early strength.
[0006] In order to solve the above technical problems, the present invention provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, which comprises, by weight: 30-50 parts of active silicate powder, 5-10 parts of reinforcing agent, 0.1-0.3 parts of water reducer, 0.03-0.05 parts of smoothing agent, 5-10 parts of stone powder, 0.09-0.15 parts of cellulose, 3-5 parts of glue powder, 60-100 parts of fine aggregate, and 10-20 parts of activator; wherein the reinforcing agent is modified coal gasification slag powder.
[0007] In the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive provided by the present invention, active silicate powder generates strength under the stimulation of an activator, thereby providing basic strength for the tile adhesive; modified coal gasification slag powder is used as a reinforcing agent, and the modified coal gasification slag powder can be better combined with organic materials such as glue powder and a smoothing agent, thereby improving the strength and workability of the material, and can also improve the bonding strength of the alkali-activated material while ensuring low cost; the water reducer can reduce the water consumption of the tile adhesive; the smoothing agent can improve the smoothness of construction, making the construction process more convenient and labor-saving; the stone powder can improve the density of the tile adhesive, improve the smoothness of construction and improve the strength; the cellulose can play a role in water retention and plasticization; the glue powder can improve the bonding strength of the tile adhesive; the fine aggregate plays a role in skeleton and filling in the tile adhesive; the activator can stimulate the activity of the active silicate powder, hydrate it and generate strength.
[0008] In combination with the first aspect, the modified coal gasification slag powder is prepared according to the following method: grinding the coal gasification slag powder to a specific surface area greater than 400m 2 / kg, soaking it with sodium hydroxide solution, washing the soaked coal gasification slag powder with ethanol and water in turn, then adding the washed coal gasification slag powder into ethanol aqueous solution, stirring evenly, subsequently adding tetraethyl orthosilicate, stirring for surface modification, and then performing solid-liquid separation, collecting the solid phase and drying to obtain the modified coal gasification slag powder.
[0009] Preferably, the modified coal gasification slag powder is prepared according to the following method: grinding the coal gasification slag powder to a specific surface area greater than 400m 2 / kg, soaking it with sodium hydroxide solution, washing the soaked coal gasification slag powder with ethanol and water in turn, then adding the washed coal gasification slag powder into 30% ethanol aqueous solution in a mass volume ratio of 1:9-11, stirring evenly, then adding ethyl orthosilicate accounting for 1 / 10 of the volume of the ethanol aqueous solution, stirring for surface modification, and then performing solid-liquid separation, collecting the solid phase and drying to obtain the modified coal gasification slag powder.
[0010] Further preferably, the concentration of the sodium hydroxide solution used is 15wt%, and the soaking time is 25-35 minutes.
[0011] More preferably, after adding tetraethyl orthosilicate, stirring is performed for 1-2 hours to carry out surface modification.
[0012] The present invention adopts modified coal gasification slag powder as a reinforcing agent, which can significantly improve the flexural strength of alkali-activated materials, thereby solving the problem of easy shrinkage and cracking and high brittleness of alkali-activated cementitious materials. At the same time, the modified coal gasification slag powder can also participate in the alkali activation reaction, consume excess alkalinity in the system, and improve the compressive strength of the material.
[0013] In combination with the first aspect, the active silicate powder is selected from at least one of slag powder, yellow phosphorus slag powder and fly ash, and the specific surface area of the active silicate powder is greater than 400m 2 / kg.
[0014] The main raw materials used in the present invention, namely, slag powder, yellow phosphorus slag powder and fly ash, are all industrial solid wastes, thus avoiding the use of cement with high production cost, being both economical and environmentally friendly, and the comprehensive performance of the obtained environmentally friendly tile adhesive meets the use requirements.
[0015] In combination with the first aspect, the water reducer is selected from at least one of a naphthalene-based water reducer and a lignin sulfonate water reducer, and the lubricant is selected from at least one of a sodium lauryl sulfate powder and a calcium stearate powder.
[0016] In combination with the first aspect, the stone powder is a powder mixed with heavy calcium powder and talcum powder in equal quantities.
[0017] Preferably, the particle size of the stone powder is less than 45 μm.
[0018] In combination with the first aspect, the cellulose is selected from at least one of hydroxypropyl methylcellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
[0019] In combination with the first aspect, the gum powder is selected from at least one of guar gum and xanthan gum.
[0020] The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive provided by the present invention does not use the types of glue powder commonly used in preparing tile adhesives (such as polyvinyl alcohol, redispersible latex powder, etc.), but selects plant glue powders with excellent alkali resistance - guar gum and / or xanthan gum. This type of glue powder can still play a good bonding role even in alkali-activated materials with strong alkalinity, solving the problem that conventional glue powder is easily ineffective in a strong alkaline environment and cannot play a role in enhancing the bonding strength.
[0021] In combination with the first aspect, the fine aggregate is selected from at least one of quartz sand, dried river sand and tailings sand, and the fineness of the fine aggregate is 30-80 mesh.
[0022] In combination with the first aspect, the activator is obtained by mixing red mud, calcium hydroxide and quick-dissolving sodium silicate in a mass ratio of 1:2:1.
[0023] Preferably, the fineness of the activator is 400-600 mesh.
[0024] In order to avoid the efflorescence of alkali-activated materials, the present invention does not select water glass and sodium hydroxide commonly used in alkali-activated materials as activators, but selects a composite activator prepared by red mud, calcium hydroxide and quick-dissolving sodium silicate which have certain alkalinity but slow hydroxide dissolution. The activator can not only provide sufficient alkalinity for the alkali-activated material to promote its reaction, but also effectively avoid the occurrence of efflorescence; moreover, the activator also includes a certain amount of red mud, which provides direction for the resource utilization of solid waste material red mud, and at the same time greatly reduces the amount of water glass used, and significantly reduces the production cost.
[0025] Preferably, red mud, calcium hydroxide and instant sodium silicate are mixed in a mass ratio of 1:2:1 and ground in a ball mill for at least 20 minutes.
[0026] The present invention also provides a method for preparing the above-mentioned coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, which specifically comprises: mixing active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, glue powder, fine aggregate and activator in proportion, and then mixing and stirring with water to obtain the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive.
[0027] Preferably, the components are mixed in proportion, added to 17.5-30 parts of water and stirred evenly, and allowed to stand for 3-5 minutes.
[0028] The gasification slag enhanced alkali-activated environmentally friendly tile adhesive provided by the present invention has the following advantages: (1) It is green and environmentally friendly. The main raw material used in the environmentally friendly tile adhesive is industrial solid waste, which avoids the high-cost calcination process in cement production and is a green and environmentally friendly material; (2) The environmentally friendly tile adhesive has the characteristics of fast setting and hardening and high early strength, which reduces the problems of falling off and slipping that are prone to occur in the early stage of tile laying; (3) Smoothing agent and stone powder are added to the environmentally friendly tile adhesive. By adjusting the material ratio and using the smoothing agent prepared for the alkali-activated material, it does not affect the material strength and can make the construction smoother and more labor-saving; (4) The environmentally friendly tile adhesive obtained by the present invention is completely made of environmentally friendly materials, and the production cost is greatly reduced. It has a water immersion tensile bonding strength, heat aging tensile bonding strength or freeze-thaw cycle tensile bonding strength that is equivalent to or even better than that of the tile adhesive made of cement, and has great economic value and practical value. DETAILED DESCRIPTION
[0029] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with specific embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0030] In view of the fact that the tile adhesive currently prepared by replacing cement with alkali-activated materials still has the problems of alkali efflux, easy shrinkage and cracking, and high brittleness, and the problem that the used glue powder is easy to fail in an alkaline environment, resulting in loose bonding of tiles, the present invention provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive and a preparation method thereof. The environmentally friendly tile adhesive replaces cement with alkali-activated materials, and simultaneously adds a reinforcing agent, a self-made new composite activator, a plant glue powder and other auxiliary materials, thereby solving the problems of easy alkali efflux, shrinkage and cracking, and high brittleness of the alkali-activated materials. The obtained adhesive has the advantages of fast setting and hardening, and high early strength, while avoiding the use of a large amount of high-cost water glass, thereby greatly reducing the production cost.
[0031] The raw materials, auxiliary materials and reagents used in the following examples and comparative examples are all commercially available industrial products, and the instruments used for preparation or testing are also commonly used instruments in this industry.
[0032] Example 1
[0033] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 1:
[0034] Table 1
[0035]
[0036]
[0037] The activator is obtained by mixing red mud, calcium hydroxide and instant sodium silicate in a mass ratio of 1:2:1 and grinding the mixture in a ball mill; the modified coal gasification slag powder is prepared by grinding the coal gasification slag powder to a specific surface area greater than 400m 2 / kg, soak it in 15wt% sodium hydroxide solution for 30 minutes, wash the soaked coal gasification slag powder with ethanol and water in turn, then add the washed coal gasification slag powder into 30% ethanol aqueous solution in a mass volume ratio of 1:10, stir evenly, then add ethyl orthosilicate accounting for 1 / 10 of the volume of the ethanol aqueous solution, stir for 1h for surface modification, and then separate the solid-liquid, collect the solid phase and dry it to obtain the modified coal gasification slag powder.
[0038] The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is as follows:
[0039] Active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, glue powder, fine aggregate and activator are mixed and stirred evenly according to the proportions in Table 1 to obtain tile adhesive powder. The tile adhesive powder is added to 25 parts of water and stirred evenly, and then allowed to stand for 4 minutes.
[0040] Example 2
[0041] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 2:
[0042] Table 2
[0043]
[0044]
[0045] The preparation method of the activator used is the same as the preparation method of the activator in Example 1; the modified coal gasification slag powder used is prepared according to the following method: the coal gasification slag powder is ground to a specific surface area greater than 400m 2 / kg, soak it in 15wt% sodium hydroxide solution for 35 minutes, wash the soaked coal gasification slag powder with ethanol and water in turn, then add the washed coal gasification slag powder into 30% ethanol aqueous solution in a mass volume ratio of 1:9, stir evenly, then add ethyl orthosilicate accounting for 1 / 10 of the volume of the ethanol aqueous solution, stir for 1.5h for surface modification, and then separate the solid and liquid, collect the solid phase and dry it to obtain the modified coal gasification slag powder.
[0046] The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is as follows:
[0047] Active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, glue powder, fine aggregate and activator are mixed and stirred evenly according to the proportions in Table 1 to obtain tile adhesive powder. The tile adhesive powder is added to 18 parts of water and stirred evenly, and then allowed to stand for 5 minutes.
[0048] Example 3
[0049] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 3:
[0050] Table 3
[0051]
[0052] The preparation method of the activator used is the same as the preparation method of the activator in Example 1; the modified coal gasification slag powder used is prepared according to the following method: the coal gasification slag powder is ground to a specific surface area greater than 400m 2 / kg, soak it in 15wt% sodium hydroxide solution for 25 minutes, wash the soaked coal gasification slag powder with ethanol and water in turn, then add the washed coal gasification slag powder into 30% ethanol aqueous solution in a mass volume ratio of 1:11, stir evenly, then add ethyl orthosilicate accounting for 1 / 10 of the volume of the ethanol aqueous solution, stir for 2h for surface modification, and then separate the solid-liquid, collect the solid phase and dry it to obtain the modified coal gasification slag powder.
[0053] The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is as follows:
[0054] Active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, glue powder, fine aggregate and activator are mixed and stirred evenly according to the proportions in Table 1 to obtain tile adhesive powder. The tile adhesive powder is added to 30 parts of water and stirred evenly, and then allowed to stand for 3 minutes.
[0055] Example 4
[0056] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 4:
[0057] Table 4
[0058]
[0059] The preparation method of the activator used is the same as the preparation method of the activator in Example 1; the modified coal gasification slag powder used is prepared according to the following method: the coal gasification slag powder is ground to a specific surface area greater than 400m 2 / kg, soak it in 15wt% sodium hydroxide solution for 30 minutes, wash the soaked coal gasification slag powder with ethanol and water in turn, then add the washed coal gasification slag powder into 30% ethanol aqueous solution in a mass volume ratio of 1:10, stir evenly, then add ethyl orthosilicate accounting for 1 / 10 of the volume of the ethanol aqueous solution, stir for 2h for surface modification, and then separate the solid-liquid, collect the solid phase and dry it to obtain the modified coal gasification slag powder.
[0060] The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is as follows:
[0061] Active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, glue powder, fine aggregate and activator are mixed and stirred evenly according to the proportions in Table 1 to obtain tile adhesive powder. The tile adhesive powder is added to 25 parts of water and stirred evenly, and then allowed to stand for 4 minutes.
[0062] Example 5
[0063] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 5:
[0064] Table 5
[0065]
[0066] The preparation methods of the activator and the modified coal gasification slag powder are the same as those in Example 1. The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is the same as that in Example 1.
[0067] Example 6
[0068] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 6:
[0069] Table 6
[0070]
[0071]
[0072] The preparation methods of the activator and the modified coal gasification slag powder are the same as those in Example 1. The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is the same as that in Example 1.
[0073] Example 7
[0074] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 7:
[0075] Table 7
[0076]
[0077] The preparation methods of the activator and the modified coal gasification slag powder are the same as those in Example 1. The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is the same as that in Example 1.
[0078] Example 8
[0079] This embodiment provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the specific raw material composition and proportion of which are shown in Table 8:
[0080] Table 8
[0081]
[0082] The preparation methods of the activator and the modified coal gasification slag powder are the same as those in Example 1. The preparation method of the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive is the same as that in Example 1.
[0083] Comparative Example 1
[0084] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the raw material formula of which is similar to that of Example 1, the only difference being that an equal amount of 42.5 ordinary Portland cement is used instead of the active silicate powder, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0085] Comparative Example 2
[0086] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the raw material formula of which is similar to that of Example 1, except that no reinforcing agent is added, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0087] Comparative Example 3
[0088] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, whose raw material formula is similar to that of Example 1, except that the enhancer is an equal amount of unmodified coal gasification slag powder, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0089] Comparative Example 4
[0090] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, and its raw material formula is similar to that of Example 1, except that the type of enhancer is different: this comparative example uses calcium carbonate powder to replace the coal gasification slag powder and modifies it according to the method in Example 1 to obtain modified calcium carbonate powder, and the remaining materials and the preparation method of the adhesive are the same as the preparation method in Example 1.
[0091] Comparative Example 5
[0092] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, the raw material formula of which is similar to that of Example 1, except that no activator is added, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0093] Comparative Example 6
[0094] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, whose raw material formula is similar to that of Example 1, except that the activator used does not contain red mud, that is, the red mud is replaced by an equal amount of calcium hydroxide, and the remaining materials and the preparation method of the adhesive are the same as the preparation method in Example 1.
[0095] Comparative Example 7
[0096] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, whose raw material formula is similar to that of Example 1, except that the adhesive powder used is vinyl acetate homopolymer adhesive powder, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0097] Comparative Example 8
[0098] This comparative example provides a coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, whose raw material formula is similar to that of Example 1, except that the activator used is water glass with a modulus of 2.0 and a Baume degree of 50 degrees, and the remaining materials and the preparation method of the adhesive are the same as those in Example 1.
[0099] Test example
[0100] The performance tests were performed on the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesives obtained in Examples 1 to 8 and Comparative Examples 1 to 8, respectively. The tensile bonding strengths under different scenarios were tested according to the standard "Ceramic Tile Adhesives" (JC / T 547-2017). The test results are shown in Table 9.
[0101] Table 9
[0102]
[0103]
[0104] From the test results of Examples 1 to 8 in Table 9, it can be seen that the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive provided by the present invention has high early strength and excellent bonding strength in different scenarios, which can meet the performance requirements of tile adhesive. In addition, compared with Example 1, under the same admixture dosage, the tile adhesive obtained by preparing the alkali-activated material with active silicate powder in Comparative Example 1 has better bonding strength than the adhesive obtained by using ordinary silicate cement, indicating that for the modified coal gasification slag powder enhanced alkali-activated tile adhesive, the selection of suitable active silicate powder has a huge impact on the performance of the tile adhesive, and also proves from the side that the enhancer (modified coal gasification slag powder) provided by the present invention is used in combination with a specific active silicate powder to obtain a tile adhesive with better performance. The results of Comparative Example 2 can show that the addition of modified coal gasification slag powder can significantly improve the bonding performance of the tile adhesive using the alkali-activated material as the raw material, and effectively enhance the bonding strength of the tile adhesive prepared from the alkali-activated material. From the results of comparative example 3, it can be seen that the coal gasification slag powder can be better combined with other organic components in the tile adhesive after modification, thereby improving the bonding strength of the tile adhesive. From the results of comparative example 4, it can be seen that the tile adhesive prepared by replacing the coal gasification slag powder with calcium carbonate and modification cannot play a good role in enhancing the bonding strength of the tile adhesive. From the results of comparative example 5, it can be seen that the activity of the active silicate component in the alkali-activated material depends on the activation of the alkali activator. When the activator is not added, the bonding strength, compressive strength and flexural strength of the obtained tile adhesive are significantly reduced, accompanied by cracks. From the results of comparative example 6, it can be seen that when the formula of the composite activator is changed (removing red mud), the bonding strength, compressive strength and flexural strength of the obtained tile adhesive are reduced, accompanied by a slight alkali phenomenon. From the results of comparative example 7, it can be seen that when the glue powder used in the present invention is replaced by the more alkali-resistant plant glue powder with vinyl acetate homopolymer glue powder, different bonding strengths decrease to varying degrees, and cracks are generated, indicating that the plant glue powder is more suitable for the system. From the results of comparative example 8, it can be seen that when the composite activator in the present invention is replaced by the commonly used water glass, the compressive strength of the obtained tile adhesive is increased, but its bonding strength is significantly reduced, and alkali efflux and cracks are obvious, indicating that the composite activator used in the present invention can effectively improve the efflux and crack conditions of alkali-activated materials.
[0105] What is described above is only a preferred specific implementation manner of the present invention, but the protection scope of the present invention is not limited thereto. Any technician familiar with the technical field can make equivalent replacements or changes according to the technical scheme and inventive concept of the present invention within the technical scope disclosed by the present invention, which should be covered by the protection scope of the present invention.
Claims
1. A coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive, characterized in that: In terms of mass proportions, the composition comprises: 30-50 parts of active silicate powder, 5-10 parts of reinforcing agent, 0.1-0.3 parts of water reducing agent, 0.03-0.05 parts of smoothing agent, 5-10 parts of stone powder, 0.09-0.15 parts of cellulose, 3-5 parts of rubber powder, 60-100 parts of fine aggregate and 10-20 parts of activator; wherein the reinforcing agent is modified coal gasification slag powder.
2. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The modified coal gasification slag powder is prepared according to the following method: grinding the coal gasification slag powder to a specific surface area greater than 400m 2 / kg, soaking it with sodium hydroxide solution, washing the soaked coal gasification slag powder with ethanol and water in turn, then adding the washed coal gasification slag powder into ethanol aqueous solution, stirring evenly, subsequently adding tetraethyl orthosilicate, stirring for surface modification, and then performing solid-liquid separation, collecting the solid phase and drying to obtain the modified coal gasification slag powder.
3. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The active silicate powder is selected from at least one of slag powder, yellow phosphorus slag powder and fly ash, and the specific surface area of the active silicate powder is greater than 400m 2 / kg.
4. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The water reducer is selected from at least one of a naphthalene-based water reducer and a lignin sulfonate water reducer, and the lubricant is selected from at least one of sodium lauryl sulfate powder and calcium stearate powder.
5. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The stone powder is a powder obtained by mixing heavy calcium powder and talcum powder in equal quantities.
6. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The cellulose is selected from at least one of hydroxypropyl methylcellulose, hydroxyethyl cellulose and carboxymethyl cellulose.
7. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The gum powder is selected from at least one of guar gum and xanthan gum.
8. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to claim 1, characterized in that: The fine aggregate is selected from at least one of quartz sand, dried river sand and tailings sand, and the fineness of the fine aggregate is 30-80 meshes.
9. The coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to any one of claims 1 to 8, characterized in that: The activator is obtained by mixing red mud, calcium hydroxide and quick-dissolving sodium silicate in a mass ratio of 1:2:
1.
10. The method for preparing the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive according to any one of claims 1 to 9, characterized in that: Active silicate powder, reinforcing agent, water reducing agent, smoothing agent, stone powder, cellulose, rubber powder, fine aggregate and activator are mixed evenly according to proportion, then mixed with water and stirred evenly to obtain the coal gasification slag enhanced alkali-activated environmentally friendly tile adhesive.
Citation Information
Patent Citations
Alkali-activated fly ash dry mixed adhesive for ceramic tiles and preparation method thereof
CN106431169A
High-temperature flue gas denitration catalyst for coal gasification slag cement kiln and preparation method thereof
CN113499778A
Granular coal gasification fine slag-based adsorbing material as well as preparation method and application thereof
CN116272848A
Coal-based solid waste-based cementing material, derived high-performance concrete and preparation method
CN116768503A
Coal gasification slag unfired ceramsite and preparation method thereof
CN117417175A
Cited By
Geopolymer-based curing agent, preparation method and curing material
CN119930179A